Grain Boundaries Boost Oxygen Evolution Reaction in NiFe Electrocatalysts. Issue 2 (3rd November 2020) - Park, Hoon Kee; Ahn, Hehsang; Lee, Tae Hyung; Lee, Jae Yoon; Lee, Mi Gyoung; Lee, Sol A.; Yang, Jin Wook; Kim, Sang Jun; Ahn, Sang Hyun; Kim, Soo Young; Lee, Chul‐Ho; Park, Eun Soo; et al.
Abstract: In a polycrystalline material, the grain boundaries (GBs) can be effective active sites for catalytic reactions by providing an electrodynamically favorable surface. Previous studies have shown that grain boundary density is related to the catalytic activity of the carbon dioxide reduction reaction, but there is still no convincing evidence that the GBs provide surfaces with enhanced activity for oxygen evolution reaction (OER). Combination of various electrochemical measurements and chemical analysis reveals the GB density at surface of NiFe electrocatalysts directly affects the overall OER. In situ electrochemical microscopy vividly shows that the OER occurs mainly at the GB during overall reaction. It is observed that the reaction determining steps are altered by grain boundary densities and the meaningful work function difference between the inside of grain and GBs exists. High‐resolution transmission electron microscopy shows that extremely high index planes are exposed at the GBs, enhancing the oxygen evolution activity. The specific nature of GBs and its effects on the OER demonstrated in this study can be applied to the various polycrystalline electrocatalysts. Abstract : In situ electrochemical observation to reveal the strong dependence of oxygen evolution reaction on grain boundary density is reported for the first time. A thermodynamically favorable aspect of the grain boundary for oxygen evolution reaction (OER) compared to the grain interior is demonstrated by various analyses. The grain boundary can elevate OER performance by modifying the reaction kinetics of the rate‐determining step.